PROBLEMATIKA PENERAPAN KURIKULUM MERDEKA DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM PADA SISWA KELAS VII DI SMPN 5 BANTAN - Hartati, Lis; Chanifudin, Chanifudin (STAI Darul Qalam Tangerang, 2023)
This study discusses the problems that occur at SMPN 5 Bantan in the application of learning Islamic religious education subjects using an independent curriculum. The independent curriculum is a curriculum that aims to hone children's interests and talents from an early age by focusing on essential materials, character development, and student competencies, for that the learning method also refers to the interest and talent approach. The independent curriculum is a new curriculum that is implemented as a refinement of the previous curriculum, namely the 2013 curriculum. However, in the implementation of this independent curriculum, there are obstacles such as Islamic religious education teachers who do not understand the independent curriculum and students who have not been able to receive the independent curriculum due to changes in this new curriculum. This is very influential on the running of a learning system, especially in Islamic religious education subjects where students are asked to be more active than teachers. The formulation of the problem in the application of the independent curriculum has two problems, namely how to apply the independent curriculum in Islamic religious education subjects at SMPN 5 Bantan, the second is what are the factors that affect the problem of implementing an independent curriculum in Islamic religious education subjects. This study uses qualitative research that is descriptive, in data collection used interview, documentation, and observation techniques. The results of this study stated that the implementation of the independent curriculum at SMPN 5 Bantan has not been carried out properly because it is difficult to change the mindset or old habits in the application of learning, the difficulty in the process of preparing learning tools, and less than optimal in differentiation learning